Incentives, organization, and public economics : papers in honour of Sir James Mirrlees - Hammond, Peter J., 1945-; Myles, Gareth D.; Mirrlees, James A. (Oxford ; New York : Oxford University Press, 2000)
The work covers Corporate Diversification and Agency, Adverse Selection and Insurance with uberrima fides , Strategic Experimentation: the Undiscounted Case, Approximate Common Knowledge in a Search Model, Wealth and Welfare, Adjusting One's Standard of Living: Two-Period Models, Who Should Provide Public Goods, An Optimal Earnings Schedule, Non-linear Utility Pricing and Targeting the Poor, A Reconsideration of the Optimal Income Tax, Reassessing the Diamond-Mirrlees Efficiency Theorem, Valuing Our Future: Cost-Benefit Analysis and Sustainability, Chinese Reforms from a Comparative Perspective, Capital Structure and Imperfect Competition in Product Markets, Renegotiation In Repeated Oligopoly Interaction, Competing against Bundles, On the Optimal Location of Capital.
Includes bibliographical references and indexes.
rpm 24/04/13 gau22/05/14
Loans
Keywords: Microeconomics; Mirrlees, James A